Respuesta :

Answer:

a. a = 1, b = -5, c = -14

b. a = 1, b = -6, c = 9

c. a = -1, b = -1, c = -3

d. a = 1, b = 0, c = -1

e. a = 1, b = 0, c = -3

Step-by-step explanation:

a. x-ints at 7 and -2

this means that our quadratic equation must factor to:

[tex](x-7)(x+2) = 0[/tex]

FOIL:

[tex]x^2 + 2x - 7x - 14 = 0[/tex]

Simplify:

[tex]x^2 - 5x - 14 = 0[/tex]

a = 1, b = -5, c = -14

b. one x-int at 3

this means that the equation will factor to:

[tex](x-3)^2=0[/tex]

FOIL:

[tex]x^2 - 3x - 3x +9 = 0[/tex]

Simplify:

[tex]x^2 - 6x + 9 = 0[/tex]

a = 1, b = -6, c = 9

c. no x-int and negative y must be less than 0

This means that our vertex must be below the x-axis and our parabola must point down

There are many equations for this, but one could be:

[tex]-x^2-x-3=0[/tex]

a = -1, b = -1, c = -3

d. one positive x-int, one negative x-int

We can use any x-intercepts, so let's just use -1 and 1

The equation will factor to:

[tex](x+1)(x-1)=0[/tex]

This is a perfect square

FOIL:

[tex]x^2-1=0[/tex]

a = 1, b = 0, c = -1

e. x-int at [tex]\sqrt{3} , -\sqrt{3}[/tex]

our equation will factor to:

[tex](x+\sqrt{3} )(x-\sqrt{3)} =0[/tex]

This is also a perfect square

FOIL and you will get:

[tex]x^2 - 3 = 0[/tex]

a = 1, b = 0, c = -3

ACCESS MORE